Jiang weisheng ai qingjie/Jianku pusu qinjian jieyue
'Pay attention to hygiene, love, cleanliness/Hard work and plain living, diligent and thrifty'. First of patriotic/educational series for primary and middle schools.. ISBN 7-03-001305-0/G.83. Four posters in one plastic bag.